Long-term performance and transfer of shares on the Tunisian Stock Exchange - Rabah Gana, Marjène; El Ammari, Anis (Revue Gouvernance / Governance Review, 2009)
In this study, we examine the long-run performance of a sample of 32 Tunisian crosslisted firms on the Tunisian stock exchange over the period 1992-2006. We use several approaches and conduct robust tests. We observed a strong underperformance of 32 percent over the 36-month period following the listing, when the buy-and-hold abnormal return measure is used. The underperformance is preceded by a positive and significant return of about 20 percent on the first 5 days of listing, which persists for 6 months. We also assess the role of governance variables. The agency theory explains the behaviour of controlling stockholders when transferring stocks. Considering other control variables shows that the hypothesis of the window opportunity explains the underperformance and that the ex-ante uncertainty, measured by the age of the newly listed firm, participate in the deterioration of the long-term stock performance.